Response of common wheat to intensifying soil fertility levels - Gyuris, Kálmán; Bona, Lajos (Acta Biologica Szegediensis, 2002)
Efficient use of adequate level of nitrogen (N), phosphorus (P), and potassium (K) is essential and important part of the sustainable agricultural production. P deficiency is one of the most important yield-limiting issue in many parts of the world including large areas of the Carpathian basin area. Bread wheat is the largest crop in Hungary and its yield is significantly affected by nutrient status of the soil. This study was conducted to determine the optimum fertilizer levels of bread wheat in a low-P level, Calcisols, rich in organic matter content and N-Supply.